2020
DOI: 10.1002/app.50391
|View full text |Cite
|
Sign up to set email alerts
|

A waterproof and breathable nanofibrous membrane with thermal‐regulated property for multifunctional textile application

Abstract: In this work, a waterproof and breathable nanofibrous membrane with thermal‐regulated performance and exhibits excellent mechanical property is fabricated by coaxial electrospinning. The fiber shell is consisted of polyvinylidene fluoride (PVDF) and polyvinyl butyral (PVB), and the core is octadecane. First, well‐performed waterproof and breathable membranes are obtained by optimizing its morphology and pore structure. Then octadecane is loaded into the fibers in the form of core by coaxial electrospinning, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…PVDF polymers are the most frequently used for fabricating W&B nanofibrous membranes attributed to their inherent hydrophobicity, spinnability, mechanical properties, and corrosion resistance. [55][56][57] Yang et al first developed the PVDF W&B membranes with porosity of 76.9%, providing a mass of vapor transmitting channels and resulting in the WVTR of 11.8 kg m −2 d −1 . [58] However, owing to the lack of rough structure and large pore sizes (2.2 µm), the membranes exhibited insufficient waterproofness (44.1 kPa).…”
Section: Pvdf Nanofibrous Membranesmentioning
confidence: 99%
“…PVDF polymers are the most frequently used for fabricating W&B nanofibrous membranes attributed to their inherent hydrophobicity, spinnability, mechanical properties, and corrosion resistance. [55][56][57] Yang et al first developed the PVDF W&B membranes with porosity of 76.9%, providing a mass of vapor transmitting channels and resulting in the WVTR of 11.8 kg m −2 d −1 . [58] However, owing to the lack of rough structure and large pore sizes (2.2 µm), the membranes exhibited insufficient waterproofness (44.1 kPa).…”
Section: Pvdf Nanofibrous Membranesmentioning
confidence: 99%
“…BIP has also been used for thermally induced chemical cross‐linking of FPU/PAN/PVB 141 . Production of WBM by coaxial electrospinning of PVDF and PVB as fiber shell and octadecane as fiber core with the hydrostatic pressure of 59.2 kPa, WVTR of 7.846 kg m −2 d −1 , and tensile strength of 20.2 MPa was investigated by Yi et al 142 Although core‐shell electrospinning proposed in this work is a reference for multifunctional WBMs, a serious challenge will be faced for scale production due to nuzzle‐based electrospinning. By electrospinning of a mixture of PVDF, fluoroalkylsilane modified TiO 2 (F‐TiO 2 ), and the organic ultraviolet (UV) absorber (UV9), a high UV resistance WBM was developed in one step 143 .…”
Section: Waterproof Breathable Membranesmentioning
confidence: 99%
“…189 As described in the previous section, octadecane as PCM was loaded in the core of PVDF/PVB fiber obtained by coaxial electrospinning and provided 50.1 J g À1 latent heat. 142 Green core-sheath membrane consisted of paraffin emulsion, and PVA exhibited effectual preventing of wax leakage and duration of 500 thermoregulating cycles. 190 The results demonstrated that the capability of the membrane extends up to 48.35 J/g with an increment in core speed rate.…”
Section: Thermoregulating Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been carried out to improve the waterproofness [1] and breathability of fabrics [2][3][4]. These textile materials do not only have the ability to protect the wearer from rain but also to provide him with a comfortable feel by transferring moisture out of the garment [2,3,[5][6][7][8][9][10]. For waterproof breathable apparels, resistance to wind is also evaluated [2,3].…”
Section: Introductionmentioning
confidence: 99%